Analisis Dampak Event Pengoplosan BBM terhadap Return Saham PT Pertamina Geothermal Energy (PGEO) - Herbenita, Herzalina (Keizai, 2025)
This study aims to analyze the impact of the illegal fuel mixing event on PT Pertamina Geothermal Energy (PGEO) stock returns. A quantitative approach was employed, utilizing linear regression and the event study method. The event window covered four days: the event day (H), and four days after the event (H+3). The results indicate that during the observation period, the market did not react significantly to the illegal fuel mixing event in the context of PGEO's stock. This may be because investors perceived the event as not directly relevant to the company's operations. The study concludes that PGEO’s stock returns are more influenced by overall market conditions than by the specific event.